2020
DOI: 10.1152/ajpregu.00248.2019
|View full text |Cite
|
Sign up to set email alerts
|

Differential vasomotor responses to isocapnic hyperoxia: cerebral versus peripheral circulation

Abstract: Isocapnic hyperoxia (IH) evokes cerebral and peripheral hypoperfusion via both disturbance of redox homeostasis and reduction in nitric oxide (NO) bioavailability. However, it is not clear whether the magnitude of the vasomotor responses depends on the vessel network exposed to IH. To test the hypothesis that the magnitude of IH-induced reduction in peripheral blood flow (BF) may differ from the hypoperfusion response observed in the cerebral vascular network under oxygen-enriched conditions, nine healthy men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A heterogeneous cerebrovascular reactivity to fluctuations in CnormalaO2 has been documented, with hyperoxia leading to a decrease in perfusion of the anterior cerebral circulation (Mattos et al . 2019, 2020). In contrast, hypoxia provokes a greater increase in blood flow to brain areas, primarily irrigated by the posterior network of cerebral blood vessels (Binks et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A heterogeneous cerebrovascular reactivity to fluctuations in CnormalaO2 has been documented, with hyperoxia leading to a decrease in perfusion of the anterior cerebral circulation (Mattos et al . 2019, 2020). In contrast, hypoxia provokes a greater increase in blood flow to brain areas, primarily irrigated by the posterior network of cerebral blood vessels (Binks et al .…”
Section: Introductionmentioning
confidence: 99%
“…While a free radical‐mediated decrease in nitric oxide (NO) bioavailability and augmented vasomotor tone reduce CBF in response to hyperoxia (Mattos et al . 2019, 2020), the mechanisms that govern the hypoxia‐induced increase in cerebral perfusion have not been elucidated in humans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to this hypothesis, we previously showed that the brain's posterior arterial network (VA) had attenuated reactivity to isocapnic hyperoxia (Mattos et al . 2020), which hypothetically suggests that the maintenance of the brainstem perfusion would neither change nor reduce CO 2 –[H + ] washout and consequently not exert further stimulation of the central chemoreceptors. Indeed, the brain's posterior arterial network showed a reduced reactivity to poikilocapnic hyperoxia compared with the anterior cerebral circulation.…”
Section: Discussionmentioning
confidence: 99%